EFFECT OF JOB DESCRIPTION ON EMPLOYEE PERFORMANCE WITH COMPENSATION AS INTERVENING VARIABLE - Cia Cai Cen (Bajang Institute, 2022)
This study aims to determine how the effect of job descriptions on employee performance with compensation as an intervening variable on employees of PT. Karya Hevea Indonesia. The research method used is the method of qualitative data and quantitative data. While the data used is primary data. The data analysis method in this study uses simple linear regression analysis to obtain a comprehensive picture of the effect of job description variables on employee performance with compensation as an intervening variable for employees of PT. Karya Hevea Indonesia using the SPSS 25 for Windows program. To find out whether there is a significant effect of the independent variable on the dependent variable, a simple linear regression model is used. The results of hypothesis testing using simple regression analysis and t-test indicate that: the t-table value of the job description variable is 4.181 > the t-table value (df:38, : 5%) is 1.685 so it can be concluded that the job description has a positive effect and significant to employee performance. Furthermore, from table 4.17 it can also be seen that the t-table value of the compensation variable is 1.186 < the t-table value (df:38, : 5%) of 1.685 so it can be concluded that compensation has no significant effect on employee performance.